Research on the paths and strategies of the integrated development of culture and tourism industry in urban historical blocks - Feng Liang; Yu Pan; Yu Pan; Meilong Gu; Yamei Liu; Lei Lei (Frontiers Media S.A., 2022)
COVID-19 has brought about great impact on the global economy. Various countries have adopted different levels of spatial isolation measures to curb the spread of the epidemic. These measures not only limit the spatial flow of people and property, but also cause global anxiety and public mental health problems. Corresponding to this process, cultural demands are growing stronger and the humanistic shift in today's urban economic development also puts forward higher requirements for local culture. Historic districts are an important symbolic historical and cultural landscape of a city, and many cities regard them as important starting points for the shaping of urban characteristics and competitiveness. Taking Qingming Bridge Historical and Cultural Block in Wuxi City as an example, combined with the public's mental health needs in the context of COVID-19 and the current background of the return of humanism in urban development, and construct a more sustainable framework for the renewal and development of urban historical blocks, focusing on the integration and development of the cultural landscape and tourism in the historical block. A comprehensive analysis shows that the development of Qingming Bridge Historical and Cultural Block must be based on the comprehensive investment of "four types of resources," such as culture, land, capital, and labor, and must rely on the cooperation of the "two sectors" of culture and tourism. By earnestly respecting the above, as well as the "triple bottom line" of regional ecology, economy, and society, sustainable development can be achieved.